(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Matrix metalloproteinases are enzymes that are involved in the digestion of the components of the extracellular matrix (ECM), cell surface receptors for soluble factors and junctional proteins and physiological processes such as tissue remodeling, but also in the stimulation of tumor growth, invasion, and metastasis. Objectives:To assess the immunohistochemical expression of MMP-3 and MMP-8 in breast carcinoma and to correlate this expression with clinicopathological parameters including patient’s age, tumor size, grade, subtype, lymph node status and lymphovascular invasion. Method:Sixty-two tissue blocks of breast carcinoma specimens were collected from Al-Kadhimiya Teaching hospital and Teaching Laboratories of the Medical City Center. Three sections of 5µm thickness were taken from each block and stained with H&E and Immunohistochemically for MMP-3 and MMP-8. Results: MMP-3 and MMP-8 expression were statistically correlated with patient’s age, tumor grade, tumor size, histological subtype, lymph node involvement, and lymphovascular permeation with the exception of MMP-8 and age. Strong expression for MMP-3 was noticed in invasive carcinoma, high grade tumors, large size tumors, cases associated with positive lymph nodes and lymphovascular permeation (positive correlation). Negative expression for MMP-8 was noticed in most of the cases associated with lymphovascular permeation and positive lymph node(s) involvement by the metastatic cells (inverse relationship). Also a negative expression for MMP-8 was noticed in most cases associated with high grade, large size tumors. Conclusions:Assessment of MMP-3 in breast carcinoma reflects the grade of tumors and can predict progression of insitu to invasive cancer, lymph node involvement and lymphovascular permeation so that it may be useful additional prognostic factor. Expression of MMP-8 correlates with a lower incidence of lymph node metastasis and lymphovascular permeation and can be utilized as a marker indicating a good prognosis to these patients. Keywords:Breast carcinoma, MMP-3, MMP-8.